Progress and Perspectives on Pyrite-Derived Materials Applied in Advanced Oxidation Processes for the Elimination of Emerging Contaminants from Wastewater - Jannat Javed; Yuting Zhou; Saad Ullah; Tianjiu Gao; Caiyun Yang; Ying Han; Hao Wu (Molecules)
Emerging contaminants (ECs) in wastewater threaten environmental and human health, while conventional methods often prove inadequate. This has driven increased concern among decision makers, justifying the need for innovative and effective treatment approaches. Pyrite-derived materials have attracted great interest in advanced oxidation processes (AOPs) as catalysts because of their unique Fe-S structure, ability to undergo redox cycling, and environmental friendliness. This review explores recent advances in pyrite-derived materials for AOP applications, focusing on their synthesis, catalytic mechanisms, and pollutant degradation. It examines how pyrite activates oxidants such as hydrogen peroxide (H2O2), peracetic acid (PAA), and peroxymonosulfate (PMS) can be used to generate reactive oxygen species (ROS). The role of multi-dimensional pyrite architectures (0D–3D) in enhancing charge transfer, catalytic activity, and recyclability is also discussed. Key challenges, including catalyst stability, industrial scalability, and Fe/S leaching, are addressed alongside potential solutions. Future directions include the integration of pyrite-based catalysts with hybrid materials, as well as green synthesis to improve practical applications. This review provides researchers and engineers with valuable insights into developing sustainable wastewater treatment technologies.